1984
DOI: 10.1159/000120166
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of CSF Shunting and IQ in Children with Myelomeningocele: A Retrospective Analysis

Abstract: This paper reviews 75 infants with myelomeningocele treated either at birth or from an early age at Rainbow Babies and Children’s Hospital, for whom complete records and psychometric testing (IQ) are available (including complete summaries from referring hospitals). Three groups are compared: (1) infants without complications who were shunted for hydrocephalus (n = 41); (2) infants with complications who were shunted (n = 16), and (3) infants who were not shunted (n = 18). Complications were defined as ventric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
25
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 1 publication
3
25
0
Order By: Relevance
“…A number of studies have shown intellect to be normal in non-shunted children and well above that of children requiring shunting. 2,4 Our ® ndings agree with this, although our mean developmental quotient of 80 for nonshunted children is lower than the IQ scores in each of these studies. In our study, children who required only one shunt were no different from those not shunted, whereas the group shunted more than once functioned signi® cantly lower in all sub-tests.…”
Section: Discussionsupporting
confidence: 86%
“…A number of studies have shown intellect to be normal in non-shunted children and well above that of children requiring shunting. 2,4 Our ® ndings agree with this, although our mean developmental quotient of 80 for nonshunted children is lower than the IQ scores in each of these studies. In our study, children who required only one shunt were no different from those not shunted, whereas the group shunted more than once functioned signi® cantly lower in all sub-tests.…”
Section: Discussionsupporting
confidence: 86%
“…3,15,35 The clinical consequences of a shunt infection include seizures, psychomotor retardation, reduced intelligence quotient, and increased mortality. 13,22,25,32,37,39 The rate of shunt infection reported varies considerably in the literature, but in recent studies the incidence typically ranges from 5% to 15%, with rates typically higher in high-risk groups such as preterm neonates and patients recently treated for shunt infection. 28,33,34,36,42 Evidence of a shunt infection often manifests within 2 months after surgery.…”
mentioning
confidence: 99%
“…14,15 Interpreting such retrospective studies to help make decisions on individual patients leads to diculty because the shunted group presumably had more severe hydrocephalus initially. The biologic cost of untreated hydrocephalus must be evaluated.…”
Section: ± 13mentioning
confidence: 99%